SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Recovery of diverse solid wastes into porous materials via thermal processing: Review of melt structure, processing parameter, and application - Weiyi Ji; Yifan Zhou; Jian-Xin Lu; Christopher Cheeseman; Chi-Sun Poon (Waste Management, 2026)

Ex ante life cycle assessment of bauxite residue vitrification technology - Maria Georgiades; Cansu Özcan Kilcan; Michiel Giels; Tobias Hertel; Yiannis Pontikes; Alan H. Tkaczyk; Christopher Cheeseman; Rupert J. Myers (The International Journal of Life Cycle Assessment, 2025)
Purpose The increasing need for novel technologies with reduced environmental impacts is driving a need for early assessment of their environmental performance, both for evaluating their potentials and supporting early-stage technology optimization. Here, we quantify the environmental performance of an emerging vitrification technology for recycling bauxite residue into a supplementary cementitious material using ex ante life cycle assessment (LCA). Methods We determine the influence of scale (i.e., laboratory, pilot, and industrial) and upscaling approach (i.e., process modeling, regression analysis, and proxy technology) on the environmental performance of this emerging vitrification technology. We produced industrial-scale LCA results at year 2050 by incorporating background changes defined using electricity mixes consistent with shared socioeconomic pathway 2 (SSP2) baseline, representative climate pathway 1.9 (RCP1.9), and SSP2 RCP2.6 scenarios, which are consistent with ~ 1.5–4.2 °C warming by 2100 relative to 1980. Results and discussion The results show significant reductions in environmental impacts from technology upscaling, of > 94% from laboratory to industrial scale, and ~ 83% from pilot to industrial scale. Upscaling resulted in low to moderate variances across most impact categories. Higher energy demands and fossil fuel-based sources in proxy scenarios led to significant variances. The results indicate that regression analysis and proxy technology can be comparable to process modeling if appropriate proxy technology is used, for the vitrification technology studied here. Incorporating background changes using a low carbon electricity scenario (SSP2 RCP1.9, consistent with ~ 1.5 °C warming by 2100 relative to 1980) resulted in reductions in many impact category indicators (CO 2 -eq., kg oil eq., etc.) up to ~ 94% by 2050. However, trade-offs were observed in many impact categories such as agricultural land occupation (12% increase) and material depletion (30% increase), resulting from increased biomass and wind electricity generation. Conclusions This study provides a structured framework for scaling bauxite residue (BR) vitrification from laboratory to industrial scale, demonstrating how different upscaling approaches and key parameters influence its environmental performance. By identifying trade-offs and environmental hotspots, it supports early-stage optimization and technical decision-making. The study highlights the importance of integrating future background scenarios such as electricity grid decarbonization into ex ante LCA studies of emerging technologies at future industrial scales. In BR vitrification, these background changes had a major influence on the projected environmental impacts. Together, these insights provide practical guidance for early-stage improvement of BR vitrification technology and are relevant for other emerging technologies in foundation industries (e.g., cement, metals, ceramics).

Characterization of daytime resting sites of New England and eastern cottontails - Kaylee Boland; Drew V. Eline; Jonathan B. Cohen; Christopher M. Whipps; Amanda E. Cheeseman (Mammal Research, 2025)
For cottontails (genus: Sylvilagus ), suitable resting cover provides essential food and protection, leading to higher survival rates. As such, resting cover is a common target for management actions. In the Northeastern United States, efforts to conserve New England cottontails ( Sylvilagus transitionalis ) have focused on habitat restoration, yet their resting cover needs remain uncharacterized. Current management practices for resting cover borrow from guidelines from eastern cottontails ( Sylvilagus floridanus ), risking unintentionally favoring this non-native competitor. Furthermore, invasive plants alter the composition and structure of resting habitat potentially impacting species like cottontails that rely on shrubs for forage and protection. This study characterized daytime resting site use for New England and eastern cottontails and examined the impacts of resting site use on their survival. We specifically examined factors contributing to use of a common, potentially harmful invasive shrub, Japanese barberry ( Berberis thunbergii ) for both species. We showed both species used a diversity of resting cover types and use was similar between species. Cottontails relied heavily on vegetative cover, with dense vegetation used more frequently than less dense vegetative cover. Invasive/ non-native plant species were used as resting cover more than other cover types. Use of Japanese barberry appeared to be linked to the lack of other suitable native cover and was associated with reduced survival. We demonstrated that recommendations for eastern cottontail resting cover may suit New England cottontails and emphasize the complex tradeoffs inherent in invasive species management. Invasive shrub cover provides crucial resources in the absence of other cover but may also increase vulnerability of at-risk populations.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Recycling of waste glass and incinerated sewage sludge ash in glass-ceramics - Yujie Huang; Ziwei Chen; Yunpeng Liu; Jian-Xin Lu; Zuwang Bian; Marcus Yio; Christopher Cheeseman; Fazhou Wang; Chi Sun Poon (Waste Management, 2024)

Resource recovery of waste glass and incinerated sewage sludge residues in self-foaming lightweight aggregate - Weiyi Ji; Marcus Yio; Ziwei Chen; Jian-Xin Lu; Christopher Cheeseman; Chi-Sun Poon (Resources, Conservation and Recycling, 2023)

Prospective life cycle assessment of European cement production - Maria Georgiades; Izhar Hussain Shah; Bernhard Steubing; Christopher Cheeseman; Rupert J. Myers (Resources, Conservation and Recycling, 2023)

Separating Proactive Conservation from Species Listing Decisions - Adrienne I. Kovach; Amanda E. Cheeseman; Jonathan B. Cohen; Chadwick D. Rittenhouse; Christopher M. Whipps (Environmental Management, 2022)
Proactive Conservation is a paradigm of natural resource management in the United States that encourages voluntary, collaborative efforts to restore species before they need to be protected through government regulations. This paradigm is widely used to conserve at-risk species today, and when used in conjunction with the Policy for Evaluation of Conservation Efforts (PECE), it allows for successful conservation actions to preclude listing of species under the Endangered Species Act (ESA). Despite the popularity of this paradigm, and recent flagship examples of its use (e.g., greater sage grouse, Centrocercus urophasianus ), critical assessments of the outcomes of Proactive Conservation are lacking from the standpoint of species status and recovery metrics. Here, we provide such an evaluation, using the New England cottontail ( Sylvilagus transitionalis ), heralded as a success of Proactive Conservation efforts in the northeastern United States, as a case study. We review the history and current status of the species, based on the state of the science, in the context of the Conservation Initiative, and the 2015 PECE decision not to the list the species under the ESA. In addition to the impacts of the PECE decision on the New England cottontail conservation specifically, our review also evaluates the benefits and limits of the Proactive Conservation paradigm more broadly, and we make recommendations for its role in relation to ESA implementation for the future of at-risk species management. We find that the status and assurances for recovery under the PECE policy, presented at the time of the New England cottontail listing decision, were overly optimistic, and the status of the species has worsened in subsequent years. We suggest that use of PECE to avoid listing may occur because of the perception of the ESA as a punitive law and a misconception that it is a failure, although very few listed species have gone extinct. Redefining recovery to decouple it from delisting and instead link it to probability of persistence under recommended conservation measures would remove some of the stigma of listing, and it would strengthen the role of Species Status Assessments in endangered species conservation.

Cold-bonding process for treatment and reuse of waste materials: Technical designs and applications of pelletized products - Alberto Ferraro; Francesco Colangelo; Ilenia Farina; Marco Race; Raffaele Cioffi; Christopher Cheeseman; Massimiliano Fabbricino (Critical Reviews in Environmental Science and Technology, 2021)

Use of MID-MIX® treated sewage sludge in cement mortars and concrete - Domagoj Nakic; Drazen Vouk; Marijana Serdar; Christopher R. Cheeseman (European Journal of Environmental and Civil Engineering, 2020)

Hierarchical population structure of a rare lagomorph indicates recent fragmentation has disrupted metapopulation function - Amanda E. Cheeseman; Jonathan B. Cohen; Christopher M. Whipps; Adrienne I. Kovach; Sadie J. Ryan (Conservation Genetics, 2019)